2022
DOI: 10.1111/ijfs.16047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red rice flour addition on the rheological, textural, sensory and bioactive properties of wheat flour‐based pan breads

Abstract: Summary Red rice, rich in fibre and phenolic contents, is one of the underutilised grains. Therefore, the present study developed the wheat/red rice flour (RRF) composites followed by its utilisation in pan breads. It led to an increase in ash and fibre contents of resultant flour combinations, but gluten network became weaker. The values for water absorption were unaffected with RRF replacements ≤15% of wheat flour. Moreover, the proximate estimates of RRF added breads demonstrated increased moisture and fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…When compared to other cereals, including corn, sorghum and buckwheat, it was readily digested in its processed form (Wu et al ., 2019) and is, therefore, one of the most popular grains in life in terms of being a good source of energy (Lai et al ., 2023). Despite the fact that it is commonly consumed as a cooked grain, with recent developments in the production of rice flour such as pasta and bread (Feng et al ., 2022; Yi et al ., 2022; Iqbal et al ., 2023), one of the issues around the consumption of rice and products made from rice flour is that the refining of rice means that the products tend to have a high glycaemic index, which could be harmful to those who regularly consume these items (Boers et al ., 2015). Part of this is due to the fact that rice bran is a rich source of bioactive ingredients, however, these tend to be susceptible to development of off flavours during prolonged storage and are therefore removed during the milling stages of processing (Eng & Mohd Rozalli, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to other cereals, including corn, sorghum and buckwheat, it was readily digested in its processed form (Wu et al ., 2019) and is, therefore, one of the most popular grains in life in terms of being a good source of energy (Lai et al ., 2023). Despite the fact that it is commonly consumed as a cooked grain, with recent developments in the production of rice flour such as pasta and bread (Feng et al ., 2022; Yi et al ., 2022; Iqbal et al ., 2023), one of the issues around the consumption of rice and products made from rice flour is that the refining of rice means that the products tend to have a high glycaemic index, which could be harmful to those who regularly consume these items (Boers et al ., 2015). Part of this is due to the fact that rice bran is a rich source of bioactive ingredients, however, these tend to be susceptible to development of off flavours during prolonged storage and are therefore removed during the milling stages of processing (Eng & Mohd Rozalli, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite several efforts to reduce coconut pulp waste, coconut pulp flour is still not widely used by the community. However, it has been reported that it has nutritional potential that will contribute to the formation of multifunctional bakery products by adding it to flour (Castro et al, 2023;Iqbal et al, 2023). The protein, fat and fibre amounts of coconut flour are higher than that of refined wheat flour (Pejcz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…So, it needs to develop a new bread enriched with fermented green olive paste rich in phenolic compounds to increase its nutritional quality. The demand for functional foods is increasing day by day and functional bakery products have come to the fore more recently (Iqbal et al ., 2023; Liu et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%